“A riqueza é a castanha”: a produção e comercialização da castanha de caju no Parque Nacional dos Lençóis Maranhenses - PEREIRA, Mônica Sousa (2022)
The large region where the Lençóis Maranhenses National Park (PNLM) is located is historically occupied by families from traditional communities who carry out various activities, including the cultivation of cashew trees. The production and sale of cashew nuts (Anacardium occidentale L.) are activitiesthat have always been central to the families' economy, even before the creation of this conservation unit in 1981. Such production, in addition to generating income for the families of these communities, has contributed decisively to the regional economy. Taking as an empirical universe the community of Bom Jardim, located within the limits of the Lençóis Maranhenses National Park (PNLM), in the municipality of Barreirinhas, the present work analyzes the complex and dynamic social and economic network that combines human labor and the management of resources around the production and marketing of cashew nuts. It also pays attention to the relationships between internal and external actors that contribute to the maintenance of the cashew nut production chain in the municipality of Barreirinhas.